Evaluation of Serum Advanced Glycation End Product Levels and Microvascular Complications in Children and Adolescents with Type 1 Diabetes Mellitus - Tarık Kırkgöz; Sezer Acar; Tuncay Küme; Hatice Hilal Kırkgöz; Gülin Tabanlı; Özlem Nalbantoğlu; Ünsal Yılmaz; Aycan Ünalp; Behzat Özkan (AVES Yayincilik, 2024)
Objective: Advanced glycation end products (AGEs) are irreversible macromolecules formed by nonenzymatic reactions due to chronic hyperglycemia. The aim of this study was to assess the relationship between AGEs and the microvascular complications of children and adolescents with type 1 diabetes mellitus (T1DM). Materials and Methods: Twenty-six T1DM patients with microvascular complications and 58 complication-naive patients who were similar regarding age, sex, and pubertal status enrolled in the study. Anthropometric, biochemical, ophthalmologic, and neurologic variables were compared with serum AGEs levels by the fluorescence method. Results: There was no significant difference observed between the patients with complications and those without complications in terms of serum levels of AGEs and other biochemical parameters. However, the duration of T1DM and urine microalbumin-creatinine ratio (uACR) were significantly higher in the complication-positive group (P < .001). Serum levels of AGEs were found to be similar when retinopathy, peripheral, and optic neuropathy were separately compared with the complication-naive group (P > .05). However, patients with nephropathy had significantly higher serum levels of AGEs than patients without complications (P = .023). In addition, there was a significant positive correlation between serum AGEs levels and uACR (P = .042) but not other parameters (P > .05). Conclusion: This study is the first to evaluate the association between serum AGEs levels and microvascular complications in children and adolescents with T1DM. Our study highlights that serum AGEs levels are significantly correlated with nephropathy but not with retinopathy and neuropathy. Further long-term studies with a larger sample size are required to establish a better relationship between diabetic complications and AGEs.